Clinical examination of the depth of the gingival sulcus in primary dentition - Batırbaygil, Yıldız; Tanboğa, İlknur; Korten, Güngör; Serdaroğlu, Berna; Gökalp, Alparslan; Özen, Hüseyin (The Turkish Journal of Pediatrics, 1986)
In this study a clinical examination was carried out to determine the gingival sulcus depth in the primary dentition. Twenty-nine children aged three to six years were examined. The measurements were made only for the right half of the jaws. Each of the ten teeth were measured in six specific locations, and a total of 1740 measurements were recorded. The gingival sulcus was found to increase in depth gradually, starting with the central incisor and ending with the second molar.The mean scores of maxilla and mandible were the same. The mean sulcus depth of the entire primary dentition was 1.43 mm. In both of the jaws the posterior segments had a greater depth of sulcus than the anterior segments. The sulcus depth was less in the facial surface, which includes the labial and the buccal surfaces, than in the lingual, mesial and distal surfaces. There was no significant difference between boys and girls as regards gingival sulcus depth.
Keywords: gingival sulcus; primary dentition